2014
DOI: 10.1590/1516-635x160231-36
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the capsule type of Pasteurella multocida isolates from cases of fowl cholera by multiplex PCR and comparison with phenotypic methods

Abstract: The ability of Pasteurella multocida to invade and multiply in its host is enhanced by the presence of the capsule, one of the most important virulence factors for this bacterium. Capsular typing methods are often used in epidemiological and pathogenesis studies of this agent. Five different serogroups have been identified based on serological typing. However, such tests are laborious, and agglutination of homologous antiserum may fail. The aim of this study was to develop a multiplex PCR protocol for the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…An aliquot of BHI after an overnight incubation (1 mL) was selected for DNA extraction using the commercial kit NucleoSpin ® Tissue (MachereyNagel ® , Düren, Germany). Initially, a PCR protocol for species-specific amplification of the kmt gene was performed, as described by Townsend et al 15 Fifteen genes associated with virulence ( ompH , oma87 , sodA , sodC , hgbA , hgbB , exBD-tonB , nanB , nanH , ptfA , pfhA , toxA ), including the genes for capsule molecular typing of serogroup A ( hyaD-hyaC ), B ( bcbD ) and D ( dcbF ), were surveyed according to the multiplex PCR protocols standardized by Furian et al 16 , 17 An additional seven genes ( hsf-1 , pmHAS , fur , psl , ompA , plpB , tadD ) were surveyed according to protocols described by Ewers et al 4 and Tang et al 6 with modifications. Reference strains of P. multocida (ATCC 15742, ATCC 12945 and ATCC 12946) were selected as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…An aliquot of BHI after an overnight incubation (1 mL) was selected for DNA extraction using the commercial kit NucleoSpin ® Tissue (MachereyNagel ® , Düren, Germany). Initially, a PCR protocol for species-specific amplification of the kmt gene was performed, as described by Townsend et al 15 Fifteen genes associated with virulence ( ompH , oma87 , sodA , sodC , hgbA , hgbB , exBD-tonB , nanB , nanH , ptfA , pfhA , toxA ), including the genes for capsule molecular typing of serogroup A ( hyaD-hyaC ), B ( bcbD ) and D ( dcbF ), were surveyed according to the multiplex PCR protocols standardized by Furian et al 16 , 17 An additional seven genes ( hsf-1 , pmHAS , fur , psl , ompA , plpB , tadD ) were surveyed according to protocols described by Ewers et al 4 and Tang et al 6 with modifications. Reference strains of P. multocida (ATCC 15742, ATCC 12945 and ATCC 12946) were selected as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…Also, PCR is used to accurate, rapid detection of toxigenic P. Multocida from swabs and tissues (Carol et al, 1996). Multiplex PCR is an alternative to comparative phenotypic tests for the capsular typing of P.multocida , for simultaneous and rapid detection of genes that provides a greater capacity for strain typing (Furian et al, 2014). Therefore, Pasteurellosis is considered an important disease in camels due to its higher economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…However, in that study, unlike our study, the strains classified as untypable were negative for both the hyaluronidase and acriflavine tests. Similarly, it was found that 11 of 54 (20.37%) strains isolated during a fowl cholera outbreak in Brazil were untypable using these phenotypic tests [7].…”
Section: Discussionmentioning
confidence: 96%